(untitled) (LEGAL DIALOGICA, 2025)
This study aims 1) to obtain an overview of how the form of legal protection provided to teachers in the face of lawsuits related to criminal acts of persecution. 2) to determine the limits of disciplinary action that can be done by teachers to student. This study uses an empirical legal research type. The location of the study is at the Watampone Religious Court, on Jalan Laksamana Yos Sudarso No. 49A, Tipojong, Tanete Riattang Timur District, Bone Regency, South Sulawesi Province. The types and sources of data are Primary and Secondary Data obtained through Interview Techniques and Documentation Studies, then qualitative analysis is carried out. The results of the study indicate 1) the jurisprudence issued by the Supreme Court (MA) affirms that a teacher cannot be subject to criminal punishment when he carriers out his proffesional duties and responsibilities in the world of education. 2) Law No. 14 of 2005 on teachers and lecturers provided a legal basis for teachers. In the case of disciplinary action taken by teachers againts student states that a teacher has the freedom to sanction students in accordance with the rules of education. The recommendations. Collaboration of school institutions, government, and law enforcement officials must work together in formulating policies in terms of protecting teachers from lawsuits. Legal socialization needs to be done so that teachers are given an understanding of the law related to the rights and obligations in educating and limits in disciplining student. Abstrak: Penelitian ini bertujuan 1) untuk memperoleh gambaran tentang bagaimana bentuk perlindungan hukum yang diberikan kepada guru dalam menghadapi tuntutan hukum terkait tindak pidana penganiayaan. 2) untuk mengetahui batasan tindakan pendisiplinan yang boleh dilakukakan guru terhadap siswa. Hasil penelitian menunjukan 1) Hasil penelitian ini menunjukkan 1) Yurisprudensi yang dikeluarkan oleh Mahkamah Agung (MA) menegaskan bahwa seorang guru tidak dapat dikenakan hukuman pidana ketika ia menjalankan tugas dan tanggung jawab profesionalnya dalam dunia pendidikan. 2) Undang-Undang nomor 14 Tahun 2005 tentang Guru dan Dosen memberikan landasan hukum bagi guru dalam melaksanakan tugas dan tanggung jawabnya sebagai tenaga pendidik. Dalam hal tindakan pendisiplinanan yang dilakukan guru terhadap siswa menyatakan bahwa seorang guru memiliki kebebasan dalam memberikan sanksi terhadap siswa sesuai dengan kaidah pendidikan. Abstrak Rekomendasi penelitian. Kolaborasi institusi sekolah, pemerintah, dan aparat penegak hukum harus bersinergi dalam merumuskan kebijakan dalam hal perlindungan guru dari tuntutan hukum. Sosialisasi hukum perlu dilakukan agar guru diberikan pemahaman hukum terkait hak dan kewajiban dalam mendidik serta batasan dalam pendisiplinan siswa.